PERTUMBUHAN TANAMAN Arachis pintoy YANG DIBERI PERLAKUAN AIR KELAPA DAN PANJANG STEK - C.L. Kaunang; M. I. Pontoh (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak, 2017)
Arachis pintoy can be reproduced in generative but also vegetative way, for example through cuttage. Problems arising from this reproduction method is the difficulty to form roots. The success rate of this method depends significantly on the size of the formed callus. To analyze the content of nutrients contained in the cuttage stem, we have to cut off the stem. And then it’s necessary to find out additional factors that can influence the forming of the callus with a large percentage of rooting. One alternative solution is the provision of coconut water which believed to contain a variety of nutrients and growth substances. Therefore, we conducted a study to find out the interaction of these two factors on the growth of Arachis pintoy The purpose and goal of this research is to study and identify the growth Arachis pintoy which treated with coconut water its influences on the stem length. This research has been performed in Agrostology Lab of Animal Husbandrys Faculty of Sam Ratulangi University, during a period of 60 days. The research materials consists of Arachis pintoy, Coconut Water and soil. While the research method use 2 experimental factors: Factor A is the Coconut water, Factor B is the after-cuttage-stem length of Arachis pintoy, which arranged through completely randomized design (CRD). Each factor consists of 3 treatments, which repeated 3 times. These factors are as follows: A = volume of Coconut water, A1 = 100 ml of coconut water, A2 = 200 ml of coconut water, and A3 = 300 ml of coconut water. Factor B = stem length of Arachis pintoy, B1 = 10 cm, B2 = 15 cm, and B3 = 20 cm. And the variables which measured in this study were plant height, dry weight of roots and the roots volume. The results showed that administration of coconut water and the length of the cuttings as well as the interaction of two factors give significant effect (P < 0.05) to the growth of the number of leaves and root dry weight of the Arachis pintoy . Furthermore, coconut water does not give effect to the root volume and a combination of two factors do not impact on the growth of plant height. From the data analysis and discussion for all variables in this study , we can conclude that the best combination of growth in the number of leaves , dry weight of roots and root volume is the provision of 300 ml of coconut water and 10 cm stem length. Keywords: Arachis pintoy, coconut water and stem length